Histomorphological Spectrum of Renal Tumours in Nephrectomy Specimens - Aishvarya Jandial; Subhash Bhardwaj (Dr. Annil Mahajan, 2023)
Introduction: The kidneys are affected by various tumors amongst which, majority of renal neoplasms are reported as malignant, with renal cell carcinoma and Wilms tumor being the most commonly diagnosed entities. Material and Methods: The study comprises of 65 patients who were diagnosed as having renal tumors and were registered in the department of Pathology from 1st July 2018 to 30th September 2021. The demographic and clinicopathological data was collected and analysed carefully. Results: Of the 65 renal tumors studied, 6 (9.23%) were reported as benign and 59 (90.77%) were reported as malignant tumors, with Renal Cell Carcinoma and Wilms tumor being the most common ones. In our study, clear cell variant of renal cell carcinoma was the most common variant reported in 39 cases (60%). Majority of cases were reported in 51-60 years age group (25 cases, 38.5%) with mean age for RCC being 53 years and for Wilms tumor being 2 years. Conclusion: A wide array of renal tumors are encountered day to day on the histopathology of nephrectomy specimens, many of which may be misdiagnosed clinically, so it is very important that each and every nephrectomy specimen be subjected to a meticulous and detailed histopathological examination for a clinico-pathological correlation to ensure proper post operative management.